2019
DOI: 10.2215/cjn.11470918
|View full text |Cite
|
Sign up to set email alerts
|

Etiology and Outcomes of Thrombotic Microangiopathies

Abstract: Background and objectivesThrombotic microangiopathies constitute a diagnostic and therapeutic challenge. Secondary thrombotic microangiopathies are less characterized than primary thrombotic microangiopathies (thrombotic thrombocytopenic purpura and atypical hemolytic and uremic syndrome). The relative frequencies and outcomes of secondary and primary thrombotic microangiopathies are unknown.Design, setting, participants, & measurementsWe conducted a retrospective study in a four-hospital institution in 56… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
151
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 109 publications
(182 citation statements)
references
References 31 publications
3
151
0
3
Order By: Relevance
“…However, overall reporting was sparse with only three studies extensively providing detailed baseline characteristics. Prevalence and incidence estimates were reported in four 23,25,27,29 and six 13,[24][25][26][27][28] studies, respectively ( Figures 2 and 3). Incidence was measured per million annually in all except one study, Jenssen 2014 measured incidence per 100,000.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…However, overall reporting was sparse with only three studies extensively providing detailed baseline characteristics. Prevalence and incidence estimates were reported in four 23,25,27,29 and six 13,[24][25][26][27][28] studies, respectively ( Figures 2 and 3). Incidence was measured per million annually in all except one study, Jenssen 2014 measured incidence per 100,000.…”
Section: Resultsmentioning
confidence: 97%
“…Of the eight studies, five studies were retrospective, 13,[24][25][26][27] one study was prospective, 28 one study was cross-sectional, 29 and one study was initially crosssectional then data were collected prospectively after 2001. 23 Three studies were conducted in individuals of all ages, 13,24,27 four studies were conducted in pediatrics (<18 years old), 23,25,26,28 and one was conducted in adults (>18 years old). 29 Fremeaux-Bacchi et al (2013) included individuals of all ages; however, they reported baseline characteristics by age group (<16 years old, ≥16 years old).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is questionable whether SLE-related TMA truly exists. Recent publications have listed multiple causes and differential diagnoses for TMA 13,14 , and in their listings, SLE is mentioned as a separate entity. A slightly different viewpoint is taken here -that all known causes for TMA should be considered in a patient with TMA accompanying SLE, and that perhaps "SLE-related TMA" does not exist.…”
Section: Ledmentioning
confidence: 99%